ELA REMIND : A medicine box reminder system for elderly living alone (ELA) implementing the infrared sensor, internet of things and mobile application - Nor Saradatul Akmar, Zulkifli; Hong, Liew Yoon; Nor Syahidatul Nadiah, Ismail; Mohd Zamri, Osman; Anis Farihan, Mat Raffei (Institute of Electrical and Electronics Engineers Inc., 2022)
Studies had shown a high statistic of the elderly often forgetting to take their medicine each day due to their forgetfulness. And living alone far from their family, make things harder. As a human of 60 years old and above, they might have difficulties to remember and become alert of the medicine time. Thus, developing this ELA Remind which is a medicine box reminder system for Elderly Living Alone (ELA) by implementing the Infrared Sensor, Internet of Things and Mobile Application. By having this system, elderly will always be reminded on time to take their medicine every day without fail. In fact, it helps to check on their medication intake history to ensure that the elderly was taking the medicine as per schedule. At the same time, it helps reduce the wastage of medication as well. Besides, the most impactful element in this system is that the reminder will also be sent to the elderly's families so that they can monitor their elders remotely through the mobile application. In addition, this system will enable users or families to check back on the history of time taken of the medicine whenever needed.